What does the literature say about using electronic pillboxes for older adults? A systematic literature review - Cruz , Antonio Miguel; Aya Parra, Pedro Antonio; Bóhorquez, Andrés Felipe (Informa Healthcare, 2018)
Clinical studies used commercially well-established electronic pillboxes with a high TRL. New electronic pillboxes in development had a low TRL. The discovered outcome was mainly adherence to medication. The overall mean adherence to medication regimens for all the studies using an electronic pillbox was higher than the gold standard of a good adherence level cut-off point (mean adherence 88.8%>80%). However, we found a large variation in this variable (SD = 10.7). With regard to an older adult population’s adherence to medication regimens, for the outcome variable of those who had undergone a kidney transplant, the clinical evidence that electronic pillboxes have a positive impact was strong (1b); for those with a chronic hepatitis C medical condition, the clinical evidence was medium (3), and for those with arterial hypertension and multiple chronic (diabetes and hypertension) medical conditions, the clinical evidence was weak (5).

Los estudios clínicos utilizaron pastilleros electrónicos comercialmente bien establecidos con un alto TRL. Los nuevos pastilleros electrónicos en desarrollo tenían un TRL bajo. El resultado descubierto fue principalmente la adherencia a la medicación. La adherencia media general a los regímenes de medicación para todos los estudios que utilizaron un pastillero electrónico fue superior al estándar de oro de un punto de corte de buen nivel de adherencia (adherencia media del 88,8%>80%). Sin embargo, se encontró una gran variación en esta variable (SD = 10,7). Con respecto a la adherencia de la población de adultos mayores a los regímenes de medicación, para la variable de resultado de aquellos que habían sido sometidos a un trasplante de riñón, la evidencia clínica de que los pastilleros electrónicos tienen un impacto positivo fue fuerte (1b); para aquellos con una condición médica de hepatitis C crónica, la evidencia clínica fue media (3), y para aquellos con hipertensión arterial y múltiples condiciones médicas crónicas (diabetes e hipertensión), la evidencia clínica fue débil .
Keywords: Pastillero electrónico; Adultos mayores; Electronic pillbox; Older adults; Centered design approach; Pastillero electrónico; Adultos mayores; Enfoque de diseño centrado